LncRNA NEAT1 Promotes Vascular Endothelial Cell Dysfunction via miR-218-5p/GAB2 and Serves as a Diagnostic Biomarker for Deep Vein Thrombosis - Wang, Shuping; Wang, Fei; Ren, Juan; Yang, Hongyu (Clinical and applied thrombosis/hemostasis, 2023)
Objective Deep vein thrombosis (DVT) is a common peripheral disease. This study aimed to elucidate the diagnostic biomarker of lncRNA nuclear-enriched abundant transcript 1 (NEAT1) in the DVT, and explore possible mechanisms in Human umbilical vein endothelial cells (HUVECs). Methods 101 patients with lower extremity DVT and 82 healthy controls were enrolled. RT-qPCR was designed to resolve the mRNA levels of NEAT1, miR-218-5p, and GAB2. ROC was applied for the diagnosis of DVT. Systemic inflammation (IL-1β, IL-6, and TNF-α) and adhesion factor (SELP, VCAM-1, and ICAM-1) were examined by the ELISA. And cell proliferation, migration, and apoptosis were conducted by the CCK-8, Transwell, flow cytometry assay. The targeting relationship was validated by Dual luciferase reporter and RIP analysis. Results NEAT1 and GAB2 were upregulated in patients with DVT, while miR-218-5p was decreased (P < .01). Serum NEAT1 can identify DVT patients from healthy individuals. NEAT1 was positively correalted with fibrinolysis factors, coagulation factors, and vasoconstrictors. NEAT1 inhibited the proliferation, migration, and promoted apoptosis as well as inflammation and adhesion factors secretion of HUVECs (P < .05), but all were impaired by overexpression of miR-218-5p (P < .05). NEAT1 promoted GAB2 expression in DVT by acting as a sponge for miR-218-5p. Conclusion Elevated NEAT1 is a possible DVT diagnostic biomarker, and is implicated in vascular endothelial cell dysfunction via miR-218-5p/GAB2 axis.